NILAI-NILAI POSITIF TOKOH HALUOLEO BAGI PENGEMBANGAN KARAKTER - Heksa Biopsi Puji Hastuti (Kadera Bahasa, 2017)
The great name of a character immortalized into the title of some vital objects in a regionconsequently carries the purposeof giving role models for character development, at least for local residents. This article raises the issue of positive valuesin character of Haluoleo figure for character development. The data are descriptions of Haluoleo character taken fromHaluoleo story of Tolaki folklore which has been published, as primary data source. The data analysis is done in twosteps, namely first level semiotic readings and second level semiotic readings. From the analysis results obtained theextraction of moral values in character Haluoleo figure as follows: (1) harmonization between softness and firmness; (2)accuracy in mapping needs and self-empowering to fulfill them as well; (3) put forward the equation for the sake oftogetherness and brotherhood; (4) sincerity; (5) respect for birth; (6) humble attitude; and (7) respect and honor friendsand enemies proportionally AbstrakNama besar seorang tokoh yang diabadikan menjadi nama beberapa objek vital di suatu wilayahtentu mengemban maksud pemberian teladan bagi pengembangan karakter, setidaknya bagi wargasetempat. Artikel ini mengangkat permasalahan nilai positif dalam karakter tokoh Haluoleo bagipengembangan karakter. Data berupa deskripsi karakter tokoh Haluoleo yang diambil dari sumberdata berupa kisah Haluoleo versi cerita rakyat Tolaki yang sudah diterbitkan. Analisis data dilakukandalam dua tahap, yaitu pembacaan semiotik tingkat pertama dan pembacaan semiotik tingkat kedua.Dari hasil analisis diperoleh ekstraksi nilai positif dalam karakter tokoh Haluoleo sebagai berikut (1)harmonisasi antara kelembutan dan ketegasan; (2) ketepatan dalam memetakan kebutuhan sekaligusmemberdayakan dirinya untuk memenuhinya; (3) mengedepankan persamaan demi kebersamaandan persaudaraan; (4) ketulusan; (5) menghargai kelahiran; (6) sikap rendah hati; dan (7) menghargaidan menghormati kawan maupun lawan secara proporsional.